2021
DOI: 10.1038/s41467-021-22444-1
|View full text |Cite|
|
Sign up to set email alerts
|

A comprehensive characterization of the cell-free transcriptome reveals tissue- and subtype-specific biomarkers for cancer detection

Abstract: Cell-free RNA (cfRNA) is a promising analyte for cancer detection. However, a comprehensive assessment of cfRNA in individuals with and without cancer has not been conducted. We perform the first transcriptome-wide characterization of cfRNA in cancer (stage III breast [n = 46], lung [n = 30]) and non-cancer (n = 89) participants from the Circulating Cell-free Genome Atlas (NCT02889978). Of 57,820 annotated genes, 39,564 (68%) are not detected in cfRNA from non-cancer individuals. Within these low-noise regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
122
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(158 citation statements)
references
References 45 publications
5
122
0
Order By: Relevance
“…The use of liquid biopsies to evaluate analytes released from tumors and normal tissues into the peripheral blood may offer a solution to the challenges associated with molecular biology-based radiotherapy. Most efforts to date have focused on characterizing and tracking ctDNA, but emerging data suggest that cell-free RNA may be a complementary analyte [ 82 ]. Notably, there is also substantial interest in monitoring circulating tumor cells (CTCs) as biomarkers and predictors of cancer treatment response [ 83 ], but a detailed discussion of this approach is outside the scope of this review.…”
Section: Liquid Biopsies To Monitor Cancer Treatment Responsementioning
confidence: 99%
See 2 more Smart Citations
“…The use of liquid biopsies to evaluate analytes released from tumors and normal tissues into the peripheral blood may offer a solution to the challenges associated with molecular biology-based radiotherapy. Most efforts to date have focused on characterizing and tracking ctDNA, but emerging data suggest that cell-free RNA may be a complementary analyte [ 82 ]. Notably, there is also substantial interest in monitoring circulating tumor cells (CTCs) as biomarkers and predictors of cancer treatment response [ 83 ], but a detailed discussion of this approach is outside the scope of this review.…”
Section: Liquid Biopsies To Monitor Cancer Treatment Responsementioning
confidence: 99%
“…To date, most analysis of circulating nucleic acids has focused on tracking genetic alterations, but novel approaches are under development to detect DNA features such as methylation and fragmentation patterns (i.e., fragmentomics) [ 146 ]. Furthermore, previous reports have suggested that cancer cells [ 147 , 148 ] and normal tissues [ 82 , 149 ] release RNA into circulation. Because these non-genetic signatures are unique to their cells of origin, they could provide a novel marker of tissue-specific pathologies.…”
Section: Liquid Biopsies To Monitor Cancer Treatment Responsementioning
confidence: 99%
See 1 more Smart Citation
“…In this context, there is considerable interest in miRNAs, namely small non-coding RNAs that regulate gene expression at the post-transcriptional level. miRNAs mediate intercellular communication, and alterations in their expression profile are closely correlated with the onset and/or progression of many types of cancers [24].…”
Section: Introductionmentioning
confidence: 99%
“…However, the eld of synthetic biomarkers has not yet bene ted from DNA multiplexing due to the susceptibility of nucleic acids in vivo 10 . Even measurements of endogenous, cell-free nucleic acids are hampered by the degradation of sequences that are not protected by the nucleosome in circulation [11][12][13][14][15] . Chemicallymodi ed nucleic acids which have been primarily developed as therapeutics are less resistant to systemic degradation; however, they have not been incorporated into diagnostic platforms because they cannot be ampli ed with conventional polymerases, nor inexpensively sequenced [16][17][18] .…”
mentioning
confidence: 99%